Pemberdayaan Guru melalui Pelatihan Pemanfaatan Kecerdasan Buatan (AI) untuk Meningkatkan Kualitas Pembelajaran di Era Digital - Muhammad Munsarif; Muhammad Sam’an; Safuan Safuan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The development of competent human resources (HR) is a top priority for improving the quality of life in society. In education, teachers' ability to enhance their skills is key to successful learning. However, many teachers struggle to adapt teaching methods to the demands of the digital era, especially in utilizing Artificial Intelligence (AI) technology. AI offers innovative solutions such as personalized learning and adaptive platforms that enhance the effectiveness of teaching and learning processes. This study examines the implementation of AI-based learning models and teacher training programs in Muhammadiyah schools in Semarang. Using the Training of Trainer (ToT) approach, the program equips teachers with skills such as using adaptive learning tools and AI-based evaluation systems. The study employs a mixed-methods approach involving practical training and result evaluation. The findings reveal improved digital literacy and confidence among teachers in using AI for interactive learning. In conclusion, AI has great potential to transform education, but its success depends on comprehensive, ethical, and sustainable strategies. The ToT program serves as a strategic step to empower teachers to face educational challenges in the digital era.